Future fertility in low fertility countries - Stuart Basten; Tomá Sobotka; Krytof Zeman (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
This paper discusses results of the global survey of experts on the future of low fertility in low-fertility countries. The survey was coordinated by the Wittgenstein Centre for Demography and Global Human Capital as a part of an effort to produce global argumentbased population projections by age, sex and level of education. First we give an overview of fertility changes in major low-fertility regions. Next we outline main theoretical arguments and review a wide range of factors contributing to fertility change and variation in contemporary low-fertility settings. Subsequently, we present survey results based on 184 assessments of over 170 experts analysing 41 countries with currently low or aroundreplacement fertility and Israel. These experts provided forecasts of period total fertility rate (TFR) in 2030 and 2050, estimated 80% confidence interval of their forecast and assessed the validity and potential impact on fertility of 46 factors. We also compare expert-derived projections of the TFR trends with the forecasts formulated by the UN World Population Prospects in 2010. The survey results in combination with the feedback provided by the invited experts then serve as a basis for formulating a set of projection scenarios for all low fertility countries up until 2050, which are additionally expanded (in a simpler form) through 2200. We present these scenarios and discuss past changes in fertility differences by level of education and their potential future trends in main regions. Presented analyses and projections indicate that a global convergence of fertility to around replacement level, envisioned in the UN projections, appears unlikely. Continuing differentiation combined with partial convergence in fertility towards lower levels is suggested as a more plausible scenario, with East Asia (including China) as well as Russia expected to have sustained very low fertility below 1.5 through 2050.
Keywords: 300; Fertility; low fertility; fertility determinants; projections; uncertainty; education; highly developed countries; Europe; East Asia